Rate Coefficients For Collisional Transitions Between A Large Number Of Rotational Levels Of Disilicon Carbide (Sicsi) Colliding With Para-H2 (j = 0) - Chandra, S.
The SiCSi is considered as one of the important molecules responsible for the production of dust around the carbon-rich stars. First detection of the SiCSi has been in the envelope of red supergiant star IRC+10216. Cabrera-Gonzalez et al. (2023) have calculated collisional rate coefficients for the disilicon carbide (SiCSi) colliding with para-H2 (j = 0), in the CC (Close-Coupling) approximation, between 31 rotational levels, having energy up to 23.844 cm-1. Though the calculations are performed for the kinetic temperature of 50 K, but they are found useful for the calculations with the temperature up to 30 K. For more reliable analysis of the molecule and for large kinetic temperature in an object, the data for large number of levels are essentially required. Thus, one needs to extend the calculations for a large number of rotational levels. In the present investigation, the work of Cabrera-Gonzalez et al. (2023) has been extended for 78 rotational levels, having energy up to 61.746 cm-1. The present calculations however have been performed in the CS (Coupled-States) approximation.
Keywords: Stars